Enhancing the effectiveness of Climate Action through gender-responsive and inclusive approaches – Lessons from Guatemala for the Central American Region - Paez Valencia, Ana Maria; Valiente, Regina; Lizarazo Torres, Miguel Angel; Borrayo Perez, Andrea Surama; Martinez Baron, Deissy (2025)
This policy brief compiles lessons learned from a series of six webinars held in Guatemala, focused on integrating gender and intersectionality into climate action. Drawing on experiences shared by international organizations, public institutions, and local actors, the document analyzes actions such as the training of climate monitors, the incorporation of a masculinities approach in the forestry sector, and the participatory design of the Gender and Climate Change Action Plan, among others. It identifies structural barriers, strategies to overcome them, and concrete results, offering recommendations to strengthen more inclusive adaptation policies and programs in Guatemala and the Central American region.